Measurement of thermophysical properties with nanomaterials on the Melting/Freezing characteristics of phase change material - Harikrishnan, S.; Dhass, A. D.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier Sci Ltd, 2022)
In the present work, four formulations of the composite phase change materials (PCMs) were produced by adding 0.5 wt% of nanoparticles (NPs), and each formulation comprised one of the types of nanoparticles. Myristic acid was considered as the base material; 0.5 wt% of Al2O3, SiO2, CuO, and Ag were reckoned as the supporting materials. Al2O3, SiO2, CuO, and Ag NPs were synthesized and they were studied by different characterization techniques. The melting and freezing temperatures of myristic acid were determined in the range from 55.54 degrees C to 55.94 degrees C and from 48.42 degrees C to 48.71 degrees C, respectively. Likewise, the latent heats for melting and freezing were found to be 192.31 kJ/kg and 192.53 kJ/kg, respectively. The thermal properties of composite PCMs were evaluated with respect to weight fractions of NPs and thermal cycles. With nanomaterial dispersion, the laser flash analyzer (LFA) confirmed the thermal conductivity enhancement of myristic acid. The composite PCMs have faster melting and freezing times than pure PCMs, as stated in the results of this study.
Keywords: PCM; Melting; Freezing; Thermal Conductivity; Nanomaterials; And Myristic acid